Individual-level determinants of depressive symptoms and associated diseases history in Turkish persons aged 15 years and older: A population-based study - Phiri, Yohane V. A.; Aydın, Kemal; Yıldız, Nadire Gülçin; Motsa, Mfundi President Sebenele; Nkoka, Owen; Aydin, Halide Z.; Chao, Hsing Jasmine (Frontiers in Psychiatry, 2022)
Background Depressive symptoms are associated with both long-lasting and short-term repetitive mood disorders and affect a person's ability to function and lead a rewarding life. In addition to predisposing genetic causes, other factors such as socioeconomic and demographic factors, and chronic diseases have also been reported to associate with depression. In this study, we analyzed the association between history of chronic diseases and the presentation of depressive symptoms among Turkish individuals. Methods We employed the 2019 Turkey health survey to analyse data of 11993 individuals aged 15+ years. Depressive symptoms were assessed using the eight-item Patient Health Questionnaire (PHQ-8) coded with a binary measure, a score of <10 as less depressed and >10 as moderate-severely depressed. A number of sociodemographic characteristics were adjusted for in the analyses. Logistic regression models were used to test the association between chronic diseases and depressive symptoms in the study sample. Results Our analysis revealed that 6.24% of the 11993 participants had reported an episode of depressive symptoms. The prevalence of depressive symptoms in men was 1.85% and in women, it was 2.34 times higher. Participants who had previously reported experiencing coronary heart diseases (AOR= 7.79, 95% CI [4.96-12.23]), urinary incontinences (AOR= 7.90, 95% CI [4.93-12.66]), and liver cirrhosis (AOR= 7.50, 95% CI [4.90-10.42]) were approximately eight times likely to have depressive symptoms. Similarly, participants with Alzheimer’s (AOR=6.83, 95% CI [5.11-8.42]), kidney problems (AOR=6.63, 95% CI [4.05-10.85]), and history of allergies (AOR=6.35, 95% CI [4.28-9.23]) had approximately seven-fold odds of reporting episodes of depressive symptoms. The odds of presenting with depressive symptoms amongst participants aged ≥50 were higher than in individuals aged ≤49 years. Conclusion At individual level, gender and general health status were associated with increased odds of depression. Furthermore, a history of any of the chronic diseases, irrespective of age, was a positive predictor of depression in our study population. Our findings could help to serve as a reference for monitoring depression amongst individuals with chronic conditions, planning health resources and developing preventive and screening strategies targeting those exposed to predisposing factors.